Engineered Cytochrome c-Catalyzed Lactone-Carbene B–H Insertion - Chen, Kai; Huang, Xiongyi; Zhang, Shuo-Qing; Zhou, Andrew Z.; Kan, S. B. Jennifer; Hong, Xin; Arnold, Frances H. (Synlett, 2019)
Previous work has demonstrated that variants of a heme protein, Rhodothermus marinus cytochrome c (Rma cyt c), catalyze abiological carbene boron–hydrogen (B–H) bond insertion with high efficiency and selectivity. Here we investigated this carbon–boron bond-forming chemistry with cyclic, lactone-based carbenes. Using directed evolution, we obtained a Rma cyt c variant BORLAC that shows high selectivity and efficiency for B–H insertion of 5- and 6-membered lactone carbenes (up to 24,500 total turnovers and 97.1:2.9 enantiomeric ratio). The enzyme shows low activity with a 7-membered lactone carbene. Computational studies revealed a highly twisted geometry of the 7-membered lactone carbene intermediate relative to 5- and 6-membered ones. Directed evolution of cytochrome c together with computational characterization of key iron-carbene intermediates has allowed us to expand the scope of enzymatic carbene B–H insertion to produce new lactone-based organoborons.
Keywords: cytochrome c; carbene; organoboron; lactones; biocatalyst; directed evolution